2021
DOI: 10.1002/ijgo.13719
|View full text |Cite
|
Sign up to set email alerts
|

Premature ovarian insufficiency secondary to COVID‐19 infection: An original case report

Abstract: Synopsis This is a case of premature ovarian insufficiency, likely induced by COVID‐19. The association has not been reported to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 4 publications
0
24
0
2
Order By: Relevance
“…ACE2 is widely expressed in the female reproductive system including the ovary, uterus, vagina, and placenta so that follicle development and ovulation, luteal angiogenesis and degeneration as well as regular changes in endometrial tissue and embryo development may be influenced by COVID-19. 94 Considering the disturbance of female reproductive functions, 95 following-up and evaluation of fertility are recommended in patients with a menstrual disorder or those with a delay in pregnancy. Menstrual data analysis of women of childbearing age diagnosed with COVID-19 revealed that a menstrual volume decrease or cycle prolongation in one-fifth of patients as a consequence of transient sex hormone changes.…”
Section: Covid-19 and Gynecologymentioning
confidence: 99%
“…ACE2 is widely expressed in the female reproductive system including the ovary, uterus, vagina, and placenta so that follicle development and ovulation, luteal angiogenesis and degeneration as well as regular changes in endometrial tissue and embryo development may be influenced by COVID-19. 94 Considering the disturbance of female reproductive functions, 95 following-up and evaluation of fertility are recommended in patients with a menstrual disorder or those with a delay in pregnancy. Menstrual data analysis of women of childbearing age diagnosed with COVID-19 revealed that a menstrual volume decrease or cycle prolongation in one-fifth of patients as a consequence of transient sex hormone changes.…”
Section: Covid-19 and Gynecologymentioning
confidence: 99%
“…Although the patients were women between 42-54 years of age, and that COVID-19 can elicit premature ovarian insufficiency, 11,12 no significant clinical or analytical signs suggestive of menopause were detected in any of the participants. Even if night sweats had been due to perimenopausal symptoms, they vanished after increasing their carbohydrate intake at night.…”
Section: Discussionmentioning
confidence: 89%
“…AOAs can be detected in 24-73% of patients with POI and may appear years before POI diagnosis [41,44]. Moreover, there are some reports of POI developing after viral infections, including one case report of COVID-19-related POI and AOA formation after anti-HPV vaccination [45,46].…”
Section: Pathogenesis Of Poimentioning
confidence: 99%